Estimation of the dependencies between output quality forming mountain masses when mining spare useful fossilized (Journal of Geography and Environmental Management, 2019)
The article describes the various aspects of relationships between output quality, the mountain masses on the basis of models of themixing process near-contact varieties of digging ore reserves.